Effect of restricted feeding on compensatory growth responses in Clarias gariepinus (Burchell, 1822) - Ali, M Z; Jauncey, K (Indian Journal of Fisheries, 2011)
A four week feeding trial was carried out in a recycling water sytem to investigate the effect of restricted feeding regimes on compensatory growth and body composition in African catfish, Clarias gariepinus . A fishmeal-based diet containing 35% protein and 18 kJ g-1 gross energy (GE) was fed to triplicate groups of 30 fish. Fish were fed in five feeding schedules of 28 days : restricted 14 days + appetite 14 days; restricted 7 days + appetite 7 days; restricted 3 days + appetite 4 days; restricted 2 days + appetite 2 days. The restricted regime was achieved by feeding at the rate of 1% (maintenance ration) of their body weight per day, adjuted after weekly weighing. African catfish did not exhibit compansatory growth response under alternating periods of a feed restriction and appetite feeding. However, not sifnificant (P>0.05) values of feed and protein utilization were found under alternating periods of feed restriction and appetite feeding. Significantly higher (P<0.05) feed intake was observed in treatment with appetite throughout than those in other treatments. All the feeding schedules showed no significant differences (P>0.05) on body composition, organ indices, eviscerated carcass composition, viscera lipid and liver lipid. This study reveals that C. gariepinus failed to display compensatory growth response by alternating periods of restricted and appetite feeding.